Peningkatan Kemampuan Berpikir Kreatif dan Prestasi Belajar Matematika melalui Metode Pembelajaran Problem Possing pada Peserta Didik Kelas VIIF SMP Negeri 2 Banjarnegara Semester 2 Tahun Pelajaran 2014/2015 - Herawati, Wiwiet (LP3 Universitas Negeri Semarang, 2015)
The outline of this research issues are how the learning process, how big an increase creative thinking and the achievenment on mathematics’ studies, as well as how to change the behavior of students with Problem possing learning model on students of class VII F of 2 Banjarnegara Junior high school semester 2 school year 2014/2015. PTK lasted two cycles. The results are creative thinking ability of mathematics in cycle I and cycle II 46.88% 61.72%. The average achievement study on cycle I is 66.91 and cycle II is 75.19. Behavior changing that appears i.e. spirit and liveliness of students.